O6-methylguanine-DNA methyltransferase (MGMT) Promoter methylation is a rare event in soft tissue sarcoma - Jakob, Jens (BioMed Central, 2012)
BACKGROUND: Gene silencing of O6-methylguanine–DNA methyltransferase (MGMT) by promoter methylation improves the outcome of glioblastoma patients after combined therapy of alkylating chemotherapeutic agents and radiation. The purpose of this study was to assess the frequency of MGMT promoter methylation in soft tissue sarcoma to identify patients eligible for alkylating agent chemotherapy such as temozolomide. FINDINGS: Paraffin tumor blocks of 75 patients with representative STS subtypes were evaluated. The methylation status of the MGMT promoter was assessed by methylation-specific polymerase-chain-reaction analysis (PCR). Furthermore, immunohistochemistry was applied to verify expression of MGMT. MGMT gene silencing was assumed if MGMT promoter methylation was present and the fraction of tumor cells expressing MGMT was 20% or less. Methylation specific PCR detected methylated MGMT promoter in 10/75 cases. Immunohistochemical staining of nuclear MGMT was negative in 15/75 cases. 6/75 tumor samples showed MGMT promoter methylation and negative immunohistochemical nuclear staining of MGMT. In none of the tested STS subtypes we found a fraction of tumors with MGMT silencing exceeding 22%. CONCLUSION: MGMT gene silencing is a rare event in soft tissue sarcoma and cannot be recommended as a selection criterion for the therapy of STS patients with alkylating agents such as temozolomide.